Two Receptors, Two Isoforms, Two Cancers: Comprehensive Analysis of KIT and TrkA Expression in Neuroblastoma and Acute Myeloid Leukemia - Lebedev, Timofey D.; Vagapova, Elmira R.; Popenko, Vladimir I.; Leonova, Olga G.; Spirin, Pavel V.; Prassolov, Vladimir S. (Frontiers in Oncology, 2019)
Pediatric cancers represent a wide variety of different tumors, nonetheless they have unique features that distinguish them from adult cancers. Receptor tyrosine kinases KIT and TrkA functions in AML and NB respectively are well characterized. Nevertheless, expression of these receptors is found in both tumors, little is known about KIT function in NB and TrkA – in AML. By combining gene enrichment analysis with multidimensional scaling we showed that pediatric AMLs with t(8;21) or inv16 and high KIT expression level stand out from other AML subtypes as they share prominent transcriptomic features exclusively with KIT-overexpressing NBs. We showed that AML cell lines have predominant expression of alternative TrkAIII isoform, which reportedly has oncogenic features, while NB cell lines have dominating TrkAI-II isoforms. NB cells, on the other hand, had an abnormal ratio of KIT isoforms as opposed to AML cells. Both SCF and NGF exerted protective action against doxorubicin and cytarabine for t(8;21) AML and NB cells. We identified several gene sets both unique and common for pediatric AML and NB, those expression is associated with KIT or TrkA levels. NMU, DUSP4, RET, SUSD5, NOS1, and GABRA5 genes are differentially expressed in NBs with high KIT expression and are associated with poor survival in NB. We identified HOXA10, BAG3 and MARCKS genes that are connected with TrkA expression and are marker genes of poor outcome in AML. We also report that SLC18A2, PLXNC1, and MRPL33 genes expression is associated with TrkA or KIT expression level in both AML and NB, and these genes have prognostic value for both cancers. Thus, we provide a comprehensive characterization of TrkA and KIT expression along with the oncogenic signatures of these genes across two pediatric tumors.